Implementasi Kebijakan Earmarking Tax Pajak Rokok Dalam Meningkatkan Kontribusi Pajak Daerah Di Kab Bekasi - Diana Prihadini; Lina Marlin (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Regional autonomy and decentralization arrangements give authority to each region in its independence to increase potential and realize people’s welfare. One of the highly developed regional potentials is regional taxes, where currently the regulation is based on Law no. 28 of 2009. In terms of people’s welfare, the law mandates the allocation of funds in a certain amount for the development of tax sector activities that are collected, this policy, the amount of which is allocated is 50% of the proceeds and is used for public health services and law enforcement. The phenomenon in this study is seen from the production of cigarettes and people who actively smoke. I think it can contribute great value to tax revenues. Cigarette axcise rates that are quite large can have an impact on local tax revenues obtained from earmarking taxes from the province. The purpose of this study is to analyze the implementation of the tax fund allocation policy for cigarette taxes in Bekasi Regency which is intended for health services and law enforcement. The method used in this research is descriptive qualitative to describe and explore the problem phenomena which are the focus of this research in depth. The results of this study are the application of the cigarette tax allocation policy in Bekasi district to the compliance of executors, in this case, it is by the provisions, but the allocation has not been maximized, the realization of the desired performance and its impact. Also not optimal.